(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This paper explores the impact of local government reforms on local democracy, citizen participation, and political accountability. The objective is to assess how reforms in governance structures influence the relationship between local authorities and citizens. A mixed-methods approach was employed, combining qualitative interviews with local officials and quantitative surveys of citizens’ perceptions. Findings reveal that while reforms have generally increased citizen participation, challenges in political accountability remain due to institutional constraints. The significance of this study lies in its implications for policymakers seeking to enhance democratic governance at the local level.